Politik Penyelenggaraan Otonomi Daerah Pasca Amandemen Keempat Undang-Undang Dasar Tahun 1945 - Ali Yusran Gea (Dinasti Research, 2024)
The principle of regulating regional autonomy in the 1945 Constitution is a measure of mutual respect between the federal and state governments. This regulation ensures that the federal government will take into account the interests of each state and territory. Article 18 of the Constitution of 1945 established rules for regional autonomy, which were later codified into Law 32 of 2004 on Regional Government. Decentralization is a key component of this law, which gives local governments more leeway to govern themselves. Law 23 of 2014, which dealt with the Regional Government, superseded this one because it transferred all powers from the federal government to the states and municipalities, with the exception of matters pertaining to foreign policy, defense, security, the judiciary, and money. The goal of granting regional autonomy is to empower the regional government here, the Regent, Mayor, and Regency/City legislators so that the region can flourish economically and generate more local original income (PAD).